2018
DOI: 10.1021/acs.est.7b05718
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances in Swedish Groundwater and Surface Water: Implications for Environmental Quality Standards and Drinking Water Guidelines

Abstract: The aim of this study was to assess per- and polyfluoroalkyl substances (PFASs) in the Swedish aquatic environment, identify emission sources, and compare measured concentrations with environmental quality standards (EQS) and (drinking) water guideline values. In total, 493 samples were analyzed in 2015 for 26 PFASs (∑PFASs) in surface water, groundwater, landfill leachate, sewage treatment plant effluents and reference lakes, focusing on hot spots and drinking water sources. Highest ∑PFAS concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(67 citation statements)
references
References 51 publications
6
60
1
Order By: Relevance
“…Environmental Science: Processes & Impacts Paper products in both surface water and aquatic invertebrates. 6 : 2 FTSA was found to be associated to re training areas, but not in urban areas, 49 strengthening the theory that site K was indirectly impacted by AFFF products. As mentioned previously, the only hazardous waste facility in Sweden is located at site K, which disposes AFFF foams by incineration and might also handle AFFF contaminated soils in landlls.…”
Section: Homologue Proles Of Pfassmentioning
confidence: 58%
See 2 more Smart Citations
“…Environmental Science: Processes & Impacts Paper products in both surface water and aquatic invertebrates. 6 : 2 FTSA was found to be associated to re training areas, but not in urban areas, 49 strengthening the theory that site K was indirectly impacted by AFFF products. As mentioned previously, the only hazardous waste facility in Sweden is located at site K, which disposes AFFF foams by incineration and might also handle AFFF contaminated soils in landlls.…”
Section: Homologue Proles Of Pfassmentioning
confidence: 58%
“…br-PFHxS 7% and br-PFOS 20%). 49 The branched isomer contributions in invertebrate samples were lower compared to surface water, ranging from 0.0-6.6% for PFOA, 0.0-18% for PFHpS and 15-28% for PFOS (br-PFHxS could not be quantied). This was expected since branched isomers are more water-soluble than the linear compound and have been suggested to have a lower uptake, faster elimination and/or selective retention in biota.…”
Section: Isomer Prolesmentioning
confidence: 93%
See 1 more Smart Citation
“…21)), and long-chain PFASs clearly dominated. 20 Studies from North American land-lls from 2006 to 2009 reported that specic short-chain PFASs were amongst the most dominant in landlls, 13,15 and this has also been reported in more recent studies from elsewhere such as China, 22 Germany, 17 Sweden, 23 and Spain. 24 It is therefore anticipated based on this shi of usage and data from other countries, that short-chain PFASs are emitted to a greater extent than long-chain PFASs from Norwegian landll leachate.…”
Section: Introductionmentioning
confidence: 78%
“…On the other hand, PFHxS, PFOA and perfluorobutanoic acid (PFBA) were equally dominant in the Yangtze River water (22%, 23 % and 27%, respectively). The PFAS concentrations were generally comparable to other river water concentrations in China [24] or in the River Rhine watershed in Europe [25], but lower than other parts of the world such as Sweden [26], or India [27].…”
Section: Raw Water Qualitymentioning
confidence: 51%